Write 3 2/3 as improper fraction

Answers

Answer 1
Answer: The answer is 11/3. Multiply the denominator (3) by the whole number (3), add the numerator (2), then keep the denominator the same! You should end up with 11/3.
Answer 2
Answer:

The improper fraction of 3(2)/(3) is ⇒ 10/3.

 

The given mixed fraction is

3(2)/(3)

We know that

Every fraction is made up of two parts: the numerator and the denominator. Proper fractions and improper fractions are the two primary forms of fractions in mathematics depending on the numerator and denominator values.

An improper fraction is a type of fraction where the numerator is greater than or equal to the denominator

In order to convert it improper fraction proceed as follow

3(2)/(3)

= (3x3 + 1)/3

= (9+1)/3

= 10/3

Thus improper fraction is 10/3

Learn more about the fraction visit:

brainly.com/question/5454147

#SPJ6


Related Questions

Which type of data is best represented by a histogram?A. data sets with some common elements B. parts of a total amount C. data that are compared using bars D. frequency distributions for certain intervals
Please help with geometry
Adele has 3 64-ounce cartons of orange juice and 3 48-ounce cans of apple juice. How much juice does she have altogether?
The local ice cream shop is deciding whether or not to hire a new worker. The shop must pay the worker hourly and cover a daily cost for insurance. The cost to pay an hourly worker for one day is represented by the function y=10x+30 where x=hours. What is the slope and what does it represent?
The side length of a square ice cube is claimed to be 1.0 inches, correct to within 0.001 inch. Use linear approximation to estimate the resulting error, measured in squared inches, in the surface area of the ice cube.

The mass of a computer

Answers

the mass of a computer uses kilogram (kg) so the weight of a computer is between .68 kg and .73... Hope it helps ur out..

Find the domain of each rational expression. f(x)=5x-7/4

Answers

 f(x)=5x-(7)/(4)

The function is defined for all real numbers x

 D=R



1)\ \ \ f(x)=5x- (7)/(4) \ \ \ \Rightarrow\ \ \ D_f=R\n\n2)\ \ \ f(x)= (5x-7)/(4) \ \ \ \Rightarrow\ \ \ D_f=R

Jaleel and Lisa are simplifying the expression 2(x - 2)^2. Jaleel’s method: 2(x - 2)^2 = 2x - 4 Lisa’s method: 2(x - 2)^2 = 2x. Whose method is correct and why? a) Lisa’s method is correct because 2(x - 2) equals 2x - 2. b) Lisa’s method is correct because 2(x - 2) equals 2x. c) Jaleel is correct because 2(x - 2) equals 2x - 2. d) Jaleel is correct because 2(x - 2) equals 2x - 4.

Answers

Answer:

The correct method is **c) Jaleel is correct because 2(x - 2) equals 2x - 2.**

Here's why:

Jaleel's method correctly expands the expression 2(x - 2)^2. When you square (x - 2), you get (x - 2)(x - 2), which simplifies to x^2 - 4x + 4. Then, multiplying this by 2 gives you 2(x^2 - 4x + 4), which simplifies further to 2x^2 - 8x + 8.

Lisa's method, on the other hand, incorrectly simplifies it as 2x. This is not the correct expansion of 2(x - 2)^2, as it neglects the square of (x - 2) and simplifies it incorrectly.

So, Jaleel's method is the correct one.

1.5 inches per hour as a fraction

Answers

Answer:

3/2 inches per hour

Step-by-step explanation:

What is an equation in point-slope form of the line that passes through (-7,1) and (-3, 9)

Answers

Step-by-step explanation:

let eqn be y - y1 = m(x - x1)

m = (9 - 1)/(-3 - (-7))

m = 2

sub (-7, 1):

y - 1 = 2(x + 7)

therefore, the equation is y - 1 = 2(x + 7)

Topic: coordinate geometry

If you like to venture further, feel free to check out my insta (learntionary). I'll be constantly posting math tips and notes! Thanks!

Answer:
y=2x+15

Solution:
Refer to the diagram

What expression is not equivalent to 1/343 A. 7-1 x 7-2
B.77 x 7-10
C. 7-2 x 7-5
D. 7-5 x 72
(All expressions have an Integer either negative or positive u just can't type it correctly here and B and D or not 77 or 72 it's 7 and positive 7 and D is 7 positive 2

Answers

1 / 343
This is just equal to 
1 / 7^3 = 7^-3

A. 7^-1 * 7^-2 = 7^(-1 + -2) = 7^-3
B. 7^7 * 7^-10 = 7^( 7+ -10) = 7^-3
C. 7^-2 * 7^-5 = 7^(-2 + -5) = 7^-7
D. 7^-5 * 7^2 = 7^(-5 + 2) = 7^-3

So the correct answer is letter C. 7^-2 * 7^-5